Presynaptic inhibitory action of enkephalin on excitatory transmission in superficial dorsal horn of rat spinal cord. - Hori, Y (1992)
1. Tight-seal whole-cell recordings were made from marginal neurones visually identified in thin slices of 1- to 2-week-old rat lumbar spinal cord. Excitatory postsynaptic currents (EPSCs), either evoked by extracellular stimulation or those arising spontaneously in tetrodotoxin, i.e. miniature EPSCs (mEPSCs), were recorded after blocking inhibitory synaptic inputs with strychnine and bicuculline. 2. The EPSCs were abolished reversibly by kynurenic acid or 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX) but not affected by (+)-2-amino-5-phosphonovalerate (APV), suggesting that they were mediated by non-NMDA (N-methyl-D-aspartate) glutamate receptors. Micromolar concentrations of methionine [Met5]enkephalin reversibly reduced the magnitude of evoked EPSCs and the frequency of mEPSCs. 3. The enkephalin action on the mEPSC frequency was blocked by naloxone. A specific agonist of mu-opiate receptor, [D-Ala2,N-Me-Phe4, Gly5]enkephalin-ol (DAGO) suppressed the mEPSC frequency. In contrast, neither a delta-opiate receptor agonist, [D-Pen2, L-Pen5]enkephalin (DPLPE) nor a kappa-opiate receptor agonist, (5 alpha, 7 alpha, 8 beta)-(-)-N-methyl-N-[7-(1-pyrrolidinyl)-1- oxaspiro(4,5)-dec-8-yl]benzeneacetamide (U-69,593) significantly affected the mEPSC frequency. 4. The amplitude of mEPSCs or of currents induced by exogenous L-glutamate, was not affected by [Met5]enkephalin. It is suggested that [Met5]enkephalin presynaptically inhibits glutamatergic EPSCs by activating the mu-opiate receptor. 5. The frequency of mEPSC was reduced by about 50% by replacement of external Ca2+ with Mg2+ or by addition of Cd2+. In Ca(2+)-free-Mg2+ solution, [Met5]enkephalin did not reduce the remaining mEPSCs' frequency any further. 6. It is concluded that the opiates may suppress presynaptic Ca2+ entry, thereby inhibiting synaptic transmission.